Cytogenetics and Molecular Genetics in Pediatric Acute Lymphoblastic Leukemia (ALL) and Its Correlation with Induction Outcomes - Loganathan, Ajeitha; Bharadwaj, Rishab; Srinivasan, Arathi; Scott, Julius Xavier (South Asian Journal of Cancer, 2022)
Aims The aim was to study cytogenetics and molecular genetic profile in pediatric B-acute lymphoblastic leukemia (ALL) and correlate it with induction outcomes.Subjects and Methods A retrospective study of cytogenetics and molecular genetics of 98 children with B-cell ALL from January 2013 to May 2018 was done. Cytogenetics and molecular genetics were done in the bone marrow using multiplex reverse transcription polymerase chain reaction and G-banded karyotyping, respectively. Minimal residual disease (MRD) assessment was done at the end of induction by flowcytometry.Results Of the 98 children, 83 (84.6%) had evaluable cytogenetics, with 11 (13.25%) being abnormal karyotypes. Of the 11 abnormal karyotypes, seven children (8.4%) had hyperdiploidy, one had hypodiploidy, and three had miscellaneous findings. In molecular genetics, TEL–AML1 (ETV6/RUNX1)[t(12;21)] was the most common fusion gene abnormality (12.2% [12/98]), followed by E2A–PBX1 [t(1;19)] (5%), BCR/ABL1 [t(9;22)] (3%), and MLL–AF4 [t(4;11)] (1%). All the 98 children attained morphologic remission at the end of induction. All children with hyperdiploidy (7/7) attained remission and MRD negativity, but one expired during maintenance chemotherapy of disseminated tuberculosis. The child with hypodiploidy was MRD-positive. Three (25%) children with t (12;21) were MRD-positive. All children with Ph + ALL, t(1:19), and t(4;11) were MRD-negative. Fifty-two children had no detected abnormalities, six of whom had MRD positivity (11.5%).Conclusion Cytogenetic and molecular genetic subgrouping prognosticates ALL outcomes. Although 25% of TEL–AML + children had MRD positivity, larger studies are required to validate the same. End-of-induction MRD outcomes did not correlate with chromosomal aberrations.
Keywords: acute lymphoblastic leukemia; cytogenetics; induction; minimal residual disease; pediatric